In vitro evaluation of the anthelmintic potential of the Plantago major and Carica papaya seeds extracts using C. elegans as experimental model - García M., Erick M. (2020)
In this work the anthelmintic potential of the aqueous and hydroalcoholic extracts of two plants used in traditional medicine as antiparasitic, Carica papaya and Plantago major, commonly known as papaya and plantain, respectively, was evaluated. The results obtained showed that the extracts of both plants possess anthelmintic activity causing mortality of C. elegans, in different concentrations. Based on the determination of LC50, the hydroalcoholic extract of P. major leaves (2,663 mg / ml) induced a mortality 40.5% higher than that of the aqueous extract (4,420 mg / ml); whereas in C. papaya the aqueous extract (2,012 mg / ml) caused a mortality 40% higher than the hydroalcoholic extract (3,350 mg / ml). The results are discussed based on the anthelmintic potential of each extract.